Brazing of curved copper sheets using CuNiSnP amorphous filler metal - Jattakul, Prajak; Kanlayasiri, Kannachai (My University, 2019)
This research investigates the effect of bending stress using furnace brazing on the interfacial layer between curved copper sheets and CuNiSnP amorphous filler metal. Copper sheet curvatures were varied between 5, 10, 15, 20, and ∞ mm to manipulate the bending stress of the base metal. The thermal behaviors and phase transformations of CuNiSnP amorphous filler metal were also characterized. The results showed that crystallization of the filler metal started at 200 °C, with multiple phases formed over the course of thermal treatment. The curved radius and bending stress were inversely correlated, while the interfacial layer of brazed joints and copper sheet curvatures were positively correlated. The interfacial layer was thin in small curvature specimens and thick in large radius specimens, indicating that the bending stress in the base metal affected the reliability of brazed joints.
Keywords: Amorphous filler metal; Bending stress; Brazing; Interface; Microchannel arrays